2009
DOI: 10.1007/s11665-009-9502-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Corrosion and Ribs on Low Cycle Fatigue Behavior of Reinforcing Steel Bars S400

Abstract: The results of an experimental study for assessing the degradation of the fatigue properties of reinforcing steel bars grade S400 caused by exposure to laboratory salt spray corrosion environment are presented. For this purpose, low cycle fatigue (LCF) tests were carried out. Furthermore, the effect of ribs on the fatigue strength was recorded. Results are indicative of the catalytic impact of corrosion on LCF behavior. Since two important degradation factors such as corrosion and LCF are functions of time, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Apostolopoulos and Papadopoulos [69] have shown that a mass loss less than 2% and 3% causes 22% and 47% reduction to the number of maximum cycles required for rupture, respectively. Apostolopoulos and Pasialis [70] have studied the low cycle fatigue behavior of smooth and ribbed steel reinforcement for different degrees of corrosion. They have reported that smooth bars showed a better cyclic behavior than that of ribbed bars for low strain amplitude and up to 8% loss of mass due to corrosion.…”
Section: Effect Of Corrosion On Mechanical Properties Of Steelmentioning
confidence: 99%
“…Apostolopoulos and Papadopoulos [69] have shown that a mass loss less than 2% and 3% causes 22% and 47% reduction to the number of maximum cycles required for rupture, respectively. Apostolopoulos and Pasialis [70] have studied the low cycle fatigue behavior of smooth and ribbed steel reinforcement for different degrees of corrosion. They have reported that smooth bars showed a better cyclic behavior than that of ribbed bars for low strain amplitude and up to 8% loss of mass due to corrosion.…”
Section: Effect Of Corrosion On Mechanical Properties Of Steelmentioning
confidence: 99%
“…structures, able to easily satisfy the limitations imposed by European standards towards reasonable production costs. Apostolopoulos and Michalopoulos [16], Apostolopoulos and Papadakis [17], Al Hashemi et al [18], and others [19][20][21] highlighted the strong decrease of the dissipative capacity of bars exposed to aggressive environmental condition, that is, subjected to corrosion phenomena, with the following degradation of the global bearing capacity of the whole structure. The deterioration of the ductility was evidenced in terms of both gt (i.e., monotonic behaviour) and dissipated energy under the execution of low-cycle fatigue tests (i.e., cyclic/seismic behaviour).…”
Section: Advances In Materials Science and Engineeringmentioning
confidence: 99%
“…In reality, however, corrosion of a steel bar mainly occurs on one side of its surface (facing the concrete cover) and this usually accompanies localised corrosion (Yuan and Ji, 2009). Currently, there is no direct correlation between accelerated corrosion tests and the natural corrosion of reinforcing steels (Apostolopoulos and Pasialis, 2010;Apostolopoulos et al, 2006). In order to accurately predict the effects of corrosion on a reinforcing steel bar, it is necessary to simulate the corrosion distribution according to the corrosion pattern that occurs in a natural environment.…”
Section: Introductionmentioning
confidence: 99%